The condition of heroes: looking for the heroic figure of future astronauts - Tachibana, Koji (Frontiers in Space Technologies, 2024)
Astronauts and cosmonauts are often called heroes. The term "hero" brings to mind a figure who is excellent in one way or another. However, it remains unclear which characteristics make a person eligible as a hero because the term has been applied to various types of figures. This paper investigates the characteristics required for people to be justifiably labelled and, based on the investigation and as a case study, looks for the heroic figure of future astronauts. First, surveying the literature from ancient to modern on heroism, it analyses that heroes are considered to be exemplars from whom we can learn something to cultivate heroic characteristics within ourselves. Second, based on this survey, it proposes the five key characteristics of heroes: attempting to scale valuable new heights; challenging difficulty in the heights; risking one's own life to scale the heights; achieving the scaling the heights; and expressing the virtue of phronesis. Third, as an application of this study, it examines a desirable, heroic figure of future astronauts. Classifying four classes of future astronauts: space tourists, space businesspersons, space soldiers, and space explorers, it argues that space explorers can mostly be called heroic if they express the five characteristics and among them, in particular, the characteristic of phronesis, a power of discerning what is good for the world. It concludes that future heroic astronauts must be thoughtful about the possible results of human space explorations because their missions may have adverse outcomes, such as intensified international conflict and environmental contamination. Such heroic astronauts are not a representative of their space agencies, companies, or nations, but an exemplar for humanity from whom we could learn virtuous characteristics as human beings.